Cancer Outpatients’ Self-Care Defi cit in Greece, Based on Orem’s Theory - Adamakidou, Theodoula; Athanasopoulou, Maria; Kalokairinos, Charalambos; Kalokairinou, Athina (Univerzita Pardubice, 2016)
Introduction and Aim: The purpose of study was to investigate the self-care defi cit of cancer patients receiving outpatient health care in Greece based on Orem’s Self-Care defi cit Nursing Theory. Methods: The sample consisted of 113 patients from home care unit and outpatient unit from 2 public oncology hospitals in Athens. The questionnaire developed by researchers based on modes of intervention according to Orem’s nursing theory which are acting or doing for others, guiding physical and psychological support, maintaining an appropriate environment and teaching. The questionnaire had dichotomy answers. Statistical analysis was done with SPSS using student‘s t-test analysis and statistical signifi cance level was set to p < 0.05. Results: The 61.9% (n = 70) of sample were female, 36.3% were aged more than 70 years, while 66.3% (n = 75) were patients of day care unit. Functional status was 39.8% stage ECOG 1. Home Care’s patients focused support needs for self-care in reporting issues such as information about the treatment (p = 0.021), economic issues (p = 0.000), and practical issues such as supply of medicine (p = 0.01), rights and insurance coverage (p = 0.000). Day care unit patients had greater self-care ability, focus on meeting emotional needs such as respect (p = 0.000), attention and care by the family (p = 0.010) and teaching for changes in the environment (p = 0.028), skills development for handling O2 (p = 0.014), lymphedema care (p = 0.045) and caring for wounds (p = 0.013). Conclusions: Awareness of patients self-care different needs by nurses, could guide the careprovided, in the context of individualized and holistic approach for greatest satisfaction.
Keywords: cancer patient; day care unit; Greece; home care nursing unit; nursing care